Efeito de uma sessão de exercício intervalado de alta intensidade sobre o controle autonômico cardíaco em obesos - Leão, Davi Rodrigues (2021)
Introduction: Obesity is a disease and has grown alarmingly worldwide, bringing with it a greater increase in the risk of death and development of chronic diseases and dysfunction in the cardiac autonomic nervous system. On the other hand, high-intensity interval exercise can be an efficient method for controlling cardiovascular autonomic balance, given its influence on the sympathetic-vagal balance. Objective: To evaluate the effect of a high-intensity interval exercise session on cardiac autonomic control in individuals with obesity compared to eutrophic individuals. Methods: 11 young people (26 ± 2.5 years old) classified as obese and 11 young people (25.2 ± 3.8 years old) classified as eutrophic were evaluated, who underwent an experimental session. The HIIE session started with warm-up (5 min at 50% of HRmax) and consisted in 1 min of exercise at 92% of maximal heart rate (HRmax) and 1 min of rest, repeated 10 times. All participants underwent exercise testing, anthropometric assessment, electrocardiogram collection and blood pressure before and after the session. The data were tabulated in Excel and analyzed using the SPSS software (Statistical Package for the Social Sciences, IBM®). The values of cardiac autonomic modulation and blood pressure were assessed by the t test for dependent samples in the intragroup assessment, and the t test for independent samples in the assessment between groups. Logarithmic transformation was employed in the absolute components of RMSSD and SDDN and low frequency / high frequency autonomic balance (LF / HF). Statistical significance was set at p <0.05. Results: In the intragroup cardiovascular autonomic evaluation, HIIE promoted a reduction in obese individuals in the SDNNlog indexes (1.60 ± 0.19ms vs. 1.42 ± 0.33, p = 0.045), in the RMSSDlog (1.63 ± 0.20ms vs 1.44 ± 0.37ms, p = 0.031) and in the eutrophic group, there was a reduction in SDNNlog indices (1.72 ± 0.15ms vs. 1.48 ± 0.20, p = 0.007), in the RMSSDlog (1.76 ± 0.17ms vs. 1.43 ± 0.23ms, p = 0.001), and in the HF component (45.53 ± 19.63un vs. 23.70 ± 22.60un, p = 0.004). For the evaluation between the groups, there was no significant difference for the autonomic index. In the analysis of intragroup blood pressure in the obese, no significant difference was found, whereas in the eutrophic group, reductions in SBP were found: -11mmHg, p = 0.007; DBP: -8mmHg, p = 0.000 and MBP: -8mmHg, p = 0.002. Conclusion: The response of heart rate variability after a single bout of high intensity interval exercise session was similar between the groups evaluated.